Hydrothermal ZnO Photocatalysis for Efficient Removal of Tetracycline from Wastewater - Wan Ishak, Wan Nuraishah; Tan, Huey Ling; Abu Bakar, Noor Fitrah; Lim, Ying Pei; Ng, Law Yong; Chun, Yang Yin (ASEAN Journal of Chemical Engineering, 2025)
Tetracycline (TC), a widely used antibiotic, is increasingly detected in wastewater, posing a significant environmental and health risk. Zinc oxide nanoparticles are emerging as a promising photocatalyst for TC photodegradation due to their low cost and superior light absorption capabilities at room temperature compared to the widely used titanium dioxide (TiO2). This study explores the efficacy of hydrothermally synthesized ZnO nanoparticles in degrading TC. The photocatalytic degradation efficiency of ZnO was examined under controlled batch conditions by varying parameters like ZnO dosage (0.5-2.5 g/L), TC concentration (5-25 ppm), and light source (solar, visible, and UV). The result showed that the highest TC removal efficiency (70.17%) was achieved under UV light with 1 g/L ZnO for a 5 ppm TC solution. The synthesized ZnO nanoparticles showed excellent reusability, highlighting their potential as a cost-effective and sustainable approach for TC degradation in wastewater treatment applications.